2011
DOI: 10.1186/1747-597x-6-13
|View full text |Cite
|
Sign up to set email alerts
|

A follow-up study on the quality of alcohol dependence-related information on the web

Abstract: In order to evaluate the one-year evolution of web-based information on alcohol dependence, we re-assessed alcohol-related sites in July 2007 with the same evaluating tool that had been used to assess these sites in June 2006. Websites were assessed with a standardized form designed to rate sites on the basis of accountability, presentation, interactivity, readability, and content quality. The DISCERN scale was also used, which aimed to assist persons without content expertise in assessing the quality of writt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 23 publications
1
5
0
Order By: Relevance
“…In line with findings from research by Coquard et al (2012) indicating a lack of change in website information on alcohol dependence over a one-year period, authors of the current study found that only six out of 26 websites modified their content from the date of the original analysis (2008) to the date of the revised analysis (2013). This is concerning given the demonstrated need for websites to make improvements in the quality of information.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In line with findings from research by Coquard et al (2012) indicating a lack of change in website information on alcohol dependence over a one-year period, authors of the current study found that only six out of 26 websites modified their content from the date of the original analysis (2008) to the date of the revised analysis (2013). This is concerning given the demonstrated need for websites to make improvements in the quality of information.…”
Section: Discussionsupporting
confidence: 88%
“…Of further concern, it has been shown that websites containing inadequate information are not significantly changed to improve this information over time. For example, Coquard, Fernandez, Zullino, and Khazaal (2012) re-assessed alcohol-related websites one year after their original analysis and found a lack of change in information.…”
Section: Introductionmentioning
confidence: 99%
“…Sports betting is associated with pathological gambling [ 2 ] and is widely available on the Internet [ 3 ], one of the most important means for seeking general, medical, and gambling information [ 4 , 5 ]. There, one can find messages such as “To win at sports betting, you have to prognosticate correctly.…”
Section: Introductionmentioning
confidence: 99%
“…Probably in connection with these considerations in sport and football betting, defeats have been shown to be more often discussed than wins [ 16 ] and were commonly attributed to unlikely or random events [ 5 ] or were considered a “near win” [ 11 ], whereas wins were attributed to skills in selecting the victorious players. This interpretation probably contributes to an overestimation of betting skills [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…A further limitation involves the comparison of the 2009 version of the Kaplan & Sadock textbook (which is unlikely to contain references to anything published after 2008 at the latest) with websites examined in 2010, which could contain later references. However, there is some evidence that, although websites containing health information have the potential to be continually updated with new information, they are in fact relatively unlikely to change over time periods of 1 or 2 years (Jorm et al 2010; Coquard et al 2011).…”
Section: Discussionmentioning
confidence: 99%